2021
DOI: 10.1002/adfm.202101291
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Sensitive, Reversible, and Bidirectional Humidity Actuator by Calcium Carbonate Ionic Oligomers Incorporated Poly(Vinylidene Fluoride)

Abstract: Sensitivity and multi‐directional motivation are major two factors for developing optimized humidity‐response materials, which are promising for sensing, energy production, etc. Organic functional groups are commonly used as the water sensitive units through hydrogen bond interactions with water molecules in actuators. The multi‐coordination ability of inorganic ions implies that the inorganic ionic compounds are potentially superior water sensitive units. However, the particle forms of inorganic ionic compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 41 publications
0
50
0
Order By: Relevance
“…31,32 Tang et al prepared a humidity actuator using hydrophilic calcium carbonate oligomers and hydrophobic poly (vinylidene fluoride), exhibiting a highly sensitive and reversible actuation. 33 Another interesting strategy is to tune a desirable porous structure, providing a sufficient contact area for exposing more water-absorbed sites, and introducing more nanochannels to accelerate water transport and diffusion, thus contributing to the rapid adsorption and desorption of water molecules. 34,35 Song et al reported a single-layered polyvinyl alcohol nanofibrous actuator via the electrospinning technique, which can perform ultrasensitive and complex shape deformations responding to water/moisture.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Tang et al prepared a humidity actuator using hydrophilic calcium carbonate oligomers and hydrophobic poly (vinylidene fluoride), exhibiting a highly sensitive and reversible actuation. 33 Another interesting strategy is to tune a desirable porous structure, providing a sufficient contact area for exposing more water-absorbed sites, and introducing more nanochannels to accelerate water transport and diffusion, thus contributing to the rapid adsorption and desorption of water molecules. 34,35 Song et al reported a single-layered polyvinyl alcohol nanofibrous actuator via the electrospinning technique, which can perform ultrasensitive and complex shape deformations responding to water/moisture.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanically responsive actuators are capable of directly converting inexpensive and readily available external stimuli (e.g., chemical vapor, [1][2][3][4] light [5][6][7][8][9] ) into mechanical work, accompanied by reversible deformation of materials (e.g., expansion, contraction, bending, twisting, rolling). They have shown broad application prospects in many high-tech fields such as robots, [10,11] sensors, [12] aerospace, [13] energy storage, [14] biomedical engineering, [15] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…However, popular methods of modifying polymers with CaCO 3 nanoparticles still depend on weak interfacial attraction. It is worth noticing that amorphous CaCO 3 exhibits polymer-like flexibility, enabling it to copolymerize with polymers and also to encapsulate micelles, carbon nanodots, gold nanoparticles, macromolecules, small-molecule amino acids and fluoresceins during its crystallization [ [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ]. Therefore, we here hypothesize that powerfully welding polymer chains within CaCO 3 nanocrystal through siphoning-induced occlusion, hydration-driven crystallization and dehydration-driven compression of amorphous mesoporous CaCO 3 nanoconcretes will possibly more effectively enhance the strength and toughness of the polymer.…”
Section: Introductionmentioning
confidence: 99%